2020
DOI: 10.1038/s41598-020-67165-5
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis cryptochrome is responsive to Radiofrequency (RF) electromagnetic fields

Abstract: How living systems respond to weak electromagnetic fields represents one of the major unsolved challenges in sensory biology. Recent evidence has implicated cryptochrome, an evolutionarily conserved flavoprotein receptor, in magnetic field responses of organisms ranging from plants to migratory birds. However, whether cryptochromes fulfill the criteria to function as biological magnetosensors remains to be established. Currently, theoretical predictions on the underlying mechanism of chemical magnetoreception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…The most well-studied sensors perceiving magnetic field directly are blue light receptors, cryptochromes. 5 , 37 , 38 Cryptochromes of higher plants are known to be able to participate in light-induced electrical reactions via activation of anionic channels, 32 but, in contrast to phototropins, other blue light receptors, they are unable to cause calcium influx or directly affect proton ATPase. 39 , 40 Field perception by the cryptochromes occurs via light-driven charge separation on the cofactor of the enzyme, flavin adenine dinucleotide (FAD) followed by electron uptake by oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-studied sensors perceiving magnetic field directly are blue light receptors, cryptochromes. 5 , 37 , 38 Cryptochromes of higher plants are known to be able to participate in light-induced electrical reactions via activation of anionic channels, 32 but, in contrast to phototropins, other blue light receptors, they are unable to cause calcium influx or directly affect proton ATPase. 39 , 40 Field perception by the cryptochromes occurs via light-driven charge separation on the cofactor of the enzyme, flavin adenine dinucleotide (FAD) followed by electron uptake by oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…27 Specifically, the prediction of rf-interference has been borne out in many experiments, for example, on birds, 19,28−30 crustaceans, 31 fruit flies, 32 and plants. 33 Cryptochrome was suggested as a candidate magnetic receptor by Ritz et al, 15 because it had been found in mammalian eyes and was known to undergo the right kind of light-dependent radical reaction (as a protein in the cryptochrome/photolyase family 34 ). Cryptochromes have since been found in birds' and other species' eyes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this way, the RPM forms the basis for a sensor that is insensitive to field polarity, responsive to a narrow (but adjustable) range of magnetic field intensities, light-dependent (though the magnetosensitive step may be light-independent, cf., below), and disrupted by weak radio frequency (rf) electromagnetic fields. ,, These properties are thought to distinguish it from the magnetic particle-mediated sense . Specifically, the prediction of rf-interference has been borne out in many experiments, for example, on birds, , crustaceans, fruit flies, and plants …”
Section: Introductionmentioning
confidence: 99%
“…The biological processes in different plant species are reported to be influenced by SMFs [5,6] resulting in changes in seed germinability [7,8], root growth and development [9], seedling vigor [10], plant yield [11], and resistance to stress factors [12][13][14][15]. Similarly, exposure to EMFs is reported to affect the physiological parameters of plants involving growth and development [16][17][18][19] and actions at the molecular level such as gene expression and regulation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%